Health-Related Quality of Life in Cervical Dystonia Using EQ-5D-5L: A Large Cross-Sectional Study in China - Liang, Yan; Lin, Junyu; Hou, Yanbing; Zhang, Lingyu; Ou, Ruwei; Li, Chunyu; Wei, Qianqian; Cao, Bei; Liu, Kuncheng; Jiang, Zheng; Yang, Tianmi; Yang, Jing; et al. (Frontiers in Neurology, 2022)
Purpose: The study aimed to evaluate the health‐related quality of life (HRQoL) measured by the five‐level EuroQol‐5 dimensions (EQ‐5D‐5L) in patients with cervical dystonia, and to explore the determinants of HRQoL in patients with cervical dystonia. Methods: EQ‐5D‐5L health state profile were converted into a single aggregated “health utility” score. A calibrated visual analog scale (EQ VAS) was used for self‐rating of current health status. Multiple linear regression analysis was used to explore the factors associated with HRQoL in cervical dystonia. Results: A total of 333 patients with cervical dystonia were enrolled in the analysis, with an average age of 44.3 years old. The most common impaired dimension of health was anxiety/depression (73.6%), followed by pain/discomfort (68.2%) and usual activities (48.0%). The median health utility score was 0.80 and the median EQ VAS score was 70. Multivariate linear regression analysis indicated that disease duration and the scores of the Hamilton Depression Rating Scale (HDRS), Pittsburgh sleep quality index (PSQI), Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) Part I, and TWSTRS Part III were associated with the health utility scores. After adjusting other parameters, TWSTRS Part III score and HDRS score were significantly associated with the EQ VAS scores (P < 0.05). Conclusion: This study evaluated HRQoL in patients with cervical dystonia using the Chinese version of the EQ‐5D‐5L scale. We found that besides motor symptoms, non-motor symptoms including depression, pain and sleep quality were could be greater determinants of HRQoL in patients with cervical dystonia. Management of non‐motor symptoms therefore may help improve HRQoL in patients with cervical dystonia.